At the Crossroads of Christianity and Philosophy: St. Paul in Athens - Adamski, Bartłomiej (Filozofia Chrześcijańska, 2025)
The purpose of this article is to deepen our understanding of St Paul’s stay in Athens as well reflect upon the speech that he delivered at the Areopagus. The article aims to achieve this by focussing primarily on the rejection that was levied against St Paul by Greek philosophers (representatives of the Hellenistic Schools of Epicureanism and Stoicism) of the central Christian truth articulated by the Apostle; namely the rejection of the Resurrection. Against this rejection of the Resurrection, the relationship between Christianity and philosophy can be explored in a more intentional way. St Paul’s address to the people gathered at the Areopagus has been a topic that has been frequently studied and interpreted by many learned people throughout history. It has become an image of the theology of preaching, missiology, and even philosophy itself. The speech has even been seen as a lesson in humility that the great Apostle had to accept himself as well as a lesson in understanding the hardness of human hearts in the light of the Resurrection. It can also be construed that in presenting the encounter between St Paul and the philosophers at the Areopagus, the author of the Acts of the Apostles intended to highlight the exclusive nature of pagan wisdom in contrast to the universal saving message of the Gospels which would soon supplant Greek philosophy as the bedrock of civilization. In all of this, however, it can be argued that the reason for the fundamental discord between human wisdom in its Hellenistic form and the Christian kerygma has not been adequately explored. It would be rather simplistic to assume that the Word of God undermines philosophy or vice versa. Since St Luke so emphatically describes this entire event and presents the Areopagus as the setting for one of the greatest confrontations recorded in the Acts of the Apostles, it naturally deserves closer attention. The entire Lukan narrative in the New Testament is a great account of the Word of God beginning to penetrate the world of that time, including ‒ as it turns out ‒ the world of pagan philosophy. The purpose of this article, therefore, is to examine this significant encounter between two worlds: that of philosophy and Christianity.